Box Counting Fractal Dimension and Frequency Size Distribution of Earthquakes in the Central Himalaya Region - Tiwari, Ram Krishna; Paudyal, Harihar (Journal of Institute of Science and Technology, 2021)
To establish the relations between b-value and fractal dimension (D0) for the earthquake distribution, we study the regional variations of those parameters in the central Himalaya region. The earthquake catalog of 989 events (Mc = 4.0) from 1994.01.31 to 2020.10.28 was analyzed in the study. The study region is divided into two sub-regions (I) Region A: 27.3°N -30.3°N and 80°E -84.8°E (western Nepal and vicinity) and (II) Region B: 26.4°N -28.6°N and 84.8°E -88.4°E (eastern Nepal and vicinity). The b-value observed is within the range between 0.92 to 1.02 for region A and 0.64 to 0.74 for region B showing the homogeneous nature of the variation. The seismic a-value for those regions ranges respectively between 5.385 to 6.007 and 4.565 to 5.218. The low b-values and low seismicity noted for region B may be related with less heterogeneity and high strength in the crust. The high seismicity with average b-values obtained for region A may be related with high heterogeneity and low strength in the crust. The fractal dimension ≥1.74 for region A and ≥ 1.82 for region B indicate that the earthquakes were distributed over two-dimensional embedding space. The observed correlation between D0 and b is negative for western Nepal and positive for eastern Nepal while the correlation between D0 and a/b value is just opposite for the respective regions. The findings identify both regions as high-stress regions. The results coming from the study agree with the results of the preceding works and reveal information about the local disparity of stress and change in tectonic complexity in the central Himalaya region.